2015
DOI: 10.3389/fevo.2015.00085
|View full text |Cite
|
Sign up to set email alerts
|

The use of multiple sources of social information in contest behavior: testing the social cognitive abilities of a cichlid fish

Abstract: Theory suggests that living in large social groups with dynamic social interactions often favors the evolution of enhanced cognitive abilities. Studies of how animals assess their own contest ability commonly focus on a single cognitive task, and little is known about the diversity or co-occurrence of cognitive abilities in social species. We examined how a highly social cichlid fish Julidochromis transcriptus uses four major cognitive abilities in contest situations; direct experience, winner/loser effects, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 68 publications
(115 reference statements)
2
23
0
Order By: Relevance
“…A>B>C>D>E). Others also tested in another African cichlid fish, Julidochromis transcriptus, and Brook trout, Salvelinus fontinalis, by using similar procedure [22][23][24]. These studies revealed TI ability in fish but also conducted with the implicit limitation that TI in fish might be a specialized form of cognition to social context.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A>B>C>D>E). Others also tested in another African cichlid fish, Julidochromis transcriptus, and Brook trout, Salvelinus fontinalis, by using similar procedure [22][23][24]. These studies revealed TI ability in fish but also conducted with the implicit limitation that TI in fish might be a specialized form of cognition to social context.…”
Section: Plos Onementioning
confidence: 99%
“…Since the pioneering study on squirrel monkeys [2], researchers have conducted TI tasks among chimpanzees [10], rhesus monkeys [11], ring-tailed lemurs, mongoose lemurs [12], brown lemurs, black lemurs [13], rats [14], pigeons [6,9], hooded crows [4], jackdaws [3], pinyon jays, western scrub jays [15], Clark's nutcrackers, azure-winged magpies [16], graylag geese [17], domestic chicks [18], and paper wasps [19]. It was also demonstrated that pinyon jays, two African cichlid fish and brook trout used TI to assess dominance rank based on observed social interactions in a controlled laboratory setting [20][21][22][23][24]; however, there is no study to test TI task in fish other than social context.…”
Section: Introductionmentioning
confidence: 99%
“…For example, White and Gowan (2013) found that juvenile brook trout (Salvelinus fontinalis) in laboratory streams were able to discern their relative rank in dominance hierarchies in part by observing the outcome of interactions among pairs of other fish, a phenomenon called transitive inference. This proved most successful when the subjects had interacted directly with one of the pair (see also Hotta et al 2015 for a test with a cichlid fish). Such social learning allows fish to avoid contests and injury, thereby increasing fitness, and additional research showed that brook trout in natural streams could learn to forage on novel prey from conspecifics (White and Gowan 2014).…”
Section: Contributions In Three Subdisciplines Of Ecologymentioning
confidence: 99%
“…Often, only a knowledgeable few are needed to produce highly accurate movement decisions (Reebs 2000); however, a complete absence of such leaders may result in poor navigational accuracy or lack of directionality (Helfman and Schultz 1984). These observations, in conjunction with growing recognition of the cognitive abilities of group-living fishes (Hotta et al 2015), give credence to theories purporting the existence of spatial learning and tradition formation in some species (see Brown 2015 for a review), in which information on previously-used migration routes is thought to be passed down from older, experienced fish to younger, naïve ones, communicated within cohorts and remembered (Corten 1993). Further support for such ideas derives from evidence for time-place learning in fishes (Brännäs 2014), and experimental demonstrations of highly accurate short-and long-term memory (Brown 2001, Hotta et al 2015.…”
Section: Introductionmentioning
confidence: 99%